A complementary conventional analysis for channelized reservoirs - Escobar, Freddy Humberto; Montealegre M, Matilde (CT&F - Ciencia, Tecnología y Futuro, 2007)
Many well pressure data coming from long and narrow reservoirs which result from either fluvial deposition of faulting cannot be completely interpreted by conventional analysis since some flow regimes are not conventionally recognized yet in the oil literature. This narrow geometry allows for the simultaneous development of two linear flow regimes coming from each one of the lateral sides of the system towards the well. This has been called dual linear flow regime. If the well is off-centered with regards to the two lateral boundaries, then, one of the linear flow regimes vanishes and, then, two possibilities can be presented. Firstly, if the closer lateral boundary is close to flow the unique linear flow persists along the longer lateral boundary. It has been called single linear flow. Following this, either steady or pseudosteady states will develop. Secondly, if a constant-pressure closer lateral boundary is dealt with, then parabolic flow develops along the longer lateral boundary. Steady state has to be developed once the disturbance reaches the farther boundary. This study presents new equations for conventional analysis for the dual linear, linear and parabolic flow regimes recently introduced to the oil literature. The equations were validated by applying them to field and simulated examples.